Use of a Standardized Perioperative Care Path for Adolescent Idiopathic Scoliosis Leads to Decreased Complications and Readmissions. Issue 1 (February 2022) - Sundar, Swetha J.; Enders, Jacob J.; Bailey, Kevin A.; Gurd, David P.; Goodwin, Ryan C.; Kuivila, Thomas E.; Ballock, Robert T.; Young, Ernest Y.
Abstract : Study Design: Retrospective review of patients ages 10–18 who underwent posterior fusion for adolescent idiopathic scoliosis (AIS) at a single institution from 2014 to 2019. Objective: The aim was to evaluate a standardized Care Path to determine its effects on perioperative outcomes in patients undergoing spinal fusion for AIS. Summary of Background Data: AIS is the most common pediatric spinal deformity and thousands of posterior fusions are performed annually. Surgery presents several postoperative challenges, such as pain control, delayed mobilization, and opioid-related morbidity. Optimizing perioperative care of AIS is a high priority to reduce morbidity and improving health care efficiency. Materials and Methods: A total of 336 patients ages 10–18 were included in this study; 117 in the pre-Care Path cohort (2014–2015) and 219 in the post-Care Path cohort (2016–2019). Data compared included intraoperative details, length of stay, timing of mobilization, inpatient complications, emergency room (ER) visits, readmissions after discharge, postoperative complications, and reoperations. Results: The post-Care Path cohort had improved mobilization on postoperative day 0 (pre 16.7%, post 53.3%, P <0.00001), reduced length of stay (pre 4.14 days, post 3.36 days, P =0.00006), fewer total inpatient complications (pre 17.1%, post 8.1%, P =0.0469), and fewer instances of postoperative ileus (pre 8.5%, post 1.9%, P =0.0102). Within 60 days of surgery, the post-Care Path cohort had fewer ER visits (pre 12.8%, post 7.2%, P =0.0413), decreased postoperative infections (pre 5.1%, post 0.48%, P =0.00547), decreased readmissions (pre 6.0%, post 0.48%, P =0.0021), and decreased reoperations (pre 5.1%, post 0.96%, P =0.0195). There was a decrease in inpatient oral morphine equivalents in the Care Path cohort (pre 118.7, post 84.7, P =0.0003). Conclusions: Our Care Path for AIS patients demonstrated significant improvements in postoperative mobilization and decreases in length of stay, complications, infections, ER visits, readmissions, and reoperations.